M. J. Farrell - Hammond, P.; Nickell, S. (Review of Economic Studies, 1976)
Journal Article M. J. Farrell Get access Peter Hammond, Peter Hammond Search for other works by this author on: Oxford Academic Google Scholar Stephen Nickell Stephen Nickell Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 1, February 1976, Page 1, https://doi.org/10.1093/restud/43.1.1 Published: 01 February 1976